Efek Beberapa Jenis Biochar Pada Berbagai Takaran terhadap Pertumbuhan dan Hasil Tanaman Kunyit (Curcuma Domestica Val.) - Adrianus Simau (Fakultas Pertanian, Universitas Timor, 2021)
This study aims to determine the effect and the dose of biochar rice husk and biochar stem kirinyuh on the growth and yield of turmeric plants in the entisol semi-arid pelitian soil. KabupatenTTU. The research method used was the experimental method in the field with a single factor randomized block design (RBD). Factor 1 type of biochar type of biochar with (K0) control, (K1) 5 t/ha of rice husk biochar, (K2) 10 t/ha of rice husk biochar, (K3) 20 t/ha of rice husk biochar, (K4) turbid biochar 5 t/ha, (K5) 10 t/ha turbid biochar, and (K6) 20 t/ha turbid biochar. These factors were combined in order to obtain 7 treatment combinations with 5 replications, then obtained 35 treatments. With the following combination: K0, K1, K2, K3, K4, K5, K6 The results showed 10 t/ha and 20 t/ha biochar treatment of rice husk had a significant effect and gave the highest value for growth parameters including leaf length. the number of leaves and environmental parameters, namely the weight and volume of the soil. The 20 t/ha biochar treatment of turbid stem gave the highest value to the environmental parameter of soil acidity and was significantly different, while in the electrical conductivity parameter, soil moisture content was not significantly different. The growth parameters 10 and 20 t/ha gave the highest values for the parameters of plant height and stem diameter. Furthermore, the parameters of 5 t/ha biochar treatment yields the highest value of rhizome bud formation, stover fresh weight, and rhizome fresh weight. dry weight of simplicia. Meanwhile, the shoot dry weight parameter and harvest index of 20 t/ha biochar treatment gave the highest value.